HIGH SCHOOL STUDENTS’ ATTITUDES TOWARDS MATHEMATICS LESSONS USING THE PQ4R STRATEGY AND PROBLEM POSING MATHEMATICAL PROBLEMS - Taufiqulloh Dahlan; Darhim Darhim; Dadang Juandi; Nia Gardenia; Thesa Kandaga (KALAMATIKA Jurnal Pendidikan Matematika, 2021)
This study aimed to examine students 'attitudes or perceptions of mathematics learning, attitudes towards the Application of PQ4R (Preview, Question, Read, Reflection, Recite, Review) Learning Strategies, and problem posing mathematical problems. Data were analyzed using a qualitative descriptive data analysis, and quantitative analysis was carried out using the Likert scale. The population in this study were Year 11 students in the city of Bandung, and the sample was one of Year 11 Social classroom as the experimental class, selected by purposive sampling. The sample was given treatment using PQ4R learning. The results showed that students taking PQ4R learning had significant attitudes towards mathematics. This can be seen from the high interest and motivation. Student responses to PQ4R learning and questions were also very good. This provides good information about students' attitudes towards learning mathematics in high school so that they can apply good and correct mathematics. Learning mathematics requires an analysis of students' attitudes to feel happy and motivated in learning mathematics on an ongoing basis.